2021
DOI: 10.1038/s41467-021-24767-5
|View full text |Cite
|
Sign up to set email alerts
|

A human CD137×PD-L1 bispecific antibody promotes anti-tumor immunity via context-dependent T cell costimulation and checkpoint blockade

Abstract: Immune checkpoint inhibitors demonstrate clinical activity in many tumor types, however, only a fraction of patients benefit. Combining CD137 agonists with these inhibitors increases anti-tumor activity preclinically, but attempts to translate these observations to the clinic have been hampered by systemic toxicity. Here we describe a human CD137xPD-L1 bispecific antibody, MCLA-145, identified through functional screening of agonist- and immune checkpoint inhibitor arm combinations. MCLA-145 potently activates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 71 publications
(60 reference statements)
2
55
0
Order By: Relevance
“…Moreover, activated T cells in peripheral blood samples may also express CD137 (26,31,32), and the increased number of CD137 + CD8 + T cells in peripheral blood samples was correlated with longer DFS in patients with melanoma who were treated with ipilimumab plus nivolumab (33). Preclinical studies have also shown that there is synergistic anti-tumor activity between PD-1/PD-L1 inhibitors and activation of the CD137 signaling pathway (34). In addition, CD137 is also a potential target of immunotherapy (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, activated T cells in peripheral blood samples may also express CD137 (26,31,32), and the increased number of CD137 + CD8 + T cells in peripheral blood samples was correlated with longer DFS in patients with melanoma who were treated with ipilimumab plus nivolumab (33). Preclinical studies have also shown that there is synergistic anti-tumor activity between PD-1/PD-L1 inhibitors and activation of the CD137 signaling pathway (34). In addition, CD137 is also a potential target of immunotherapy (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…For studies in mice, most experiments established xenograft models using mouse tumor cells in immunocompetent C57BL/6 mice and BALB/c mice. Other studies used NSG mice with/without human CD34 + human stem cell-engrafted to establish xenograft models of human tumor cells [ 250 , 251 ]. However, one of the limitations of the xenograft model is that it is too far from the real process of tumorigenesis, and the conclusions obtained in those models cannot be better translated into clinical research.…”
Section: Preclinical Models Used In Research About Pd-1/pd-l1 Blockadementioning
confidence: 99%
“…VTCN1 is a transmembrane protein expressed on the surface of some tumors and is considered to negatively regulate T cells, significantly inhibiting CD4+ T cell differentiation [ 83 ]. TNFSF9 (also known as CD137 or 4-1BB) is an inducible costimulatory receptor expressed on activated T cells and natural killer cells that can enhance effective function; combining PD-1/PD-L1 blockade with a CD137 agonist synergistically increased antitumor responses [ 84 ]. We hypothesize that a combination therapy targeting immune checkpoints and pyroptosis might be a novel therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%